The prion-like protein kinase Sky1 is required for efficient stress granule disassembly - Jenifer E. Shattuck (Nature Portfolio, 2019)
The factors regulating stress granule dissolution are not fully understood. Here, the authors identify Sky1 as a stress granule component in yeast, and show that Sky1 kinase activity is required for timely stress granule disassembly during stress recovery.